2021
DOI: 10.1186/s13550-021-00760-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prediction of pathological grade in pancreatic ductal adenocarcinoma based on 18F-FDG PET/CT radiomics

Abstract: Purpose To develop and validate a machine learning model based on radiomic features derived from 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) images to preoperatively predict the pathological grade in patients with pancreatic ductal adenocarcinoma (PDAC). Methods A total of 149 patients (83 men, 66 women, mean age 61 years old) with pathologically proven PDAC and a preoperative 18F-FDG PET/CT scan betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Among the 13 selected radiomics features in the present study, it demonstrated that features extracted from wavelet transformed images play an important role in prediction models. The wavelet transform can decompose the image into low-frequency elements and/or high-frequency components at different scales, and the texture features obtained from the wavelet decomposition of the original data can signify different frequency ranges within the tumor volume [ 31 ]. Some studies have demonstrated that wavelet-based features are important in radiomics studies and can show promising capabilities in terms of tumor classification and prognosis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 13 selected radiomics features in the present study, it demonstrated that features extracted from wavelet transformed images play an important role in prediction models. The wavelet transform can decompose the image into low-frequency elements and/or high-frequency components at different scales, and the texture features obtained from the wavelet decomposition of the original data can signify different frequency ranges within the tumor volume [ 31 ]. Some studies have demonstrated that wavelet-based features are important in radiomics studies and can show promising capabilities in terms of tumor classification and prognosis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer was featured in 13 studies based on 18F-FDG [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. An average of 110.7 patients was included (range: 48–198, 8 studies with more than 100 patients) with 1 (7.7%) prospective study and 4 (30.8%) using a validation cohort.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 8 studies (61.5%) focused on prognosis, while the remaining 5 dealt with diagnostic issues and histological characterization. Promising results were found in terms of grade of tumoral differentiation prediction [ 62 ] with a model based on a twelve-feature-combined radiomics signature that could stratify pancreatic ductal adenocarcinoma patients into grade G1 and grade G2/3 groups, with an AUC of 0.994 in the training set and 0.921 in the validation set.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown data supporting the utility of PET scan in staging of pancreatic cancer[ 61 - 63 ], whereas other studies have shown conflicting results[ 64 , 65 ]. Use of 18F-flurodeoxyglucose (FDG) PET combined with CT (PET/CT) and MRI (PET/MRI) has generated interest in diagnosis, staging (lymph node involvement and metastasis)[ 66 ], assessment of pathological grade[ 67 ], assessment of treatment response, planning of radiation treatment, etc. [ 68 - 70 ].…”
Section: Diagnostic Evaluationmentioning
confidence: 99%